Problematika Peraturan Pemerintah Nomor 48 Tahun 2014 Pada Aspek Biaya Pernikahan di KUA Kecamatan Jatiasih Kota Bekasi - Damhuri, Nur Alwan; -, Suprihatin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2019)
In Indonesia, the registration of marriages for Muslims is carried out by the Office of ReligiousAffairs (KUA). The Office of Religious Affairs (KUA) is an institution at the Ministry of Religion atthe sub-district level that provides services to Muslims in matters of marriage and fostering Muslimfamilies to become sakinah families. Marriage registration is carried out by a marriage registraremployee / guardian of a marriage registrar (penghulu).Government Regulation Number 48 of 2014concerning tariffs on types of non-tax state revenue that apply to the Ministry of Religion whichregulates the rates when carrying out a marriage outside the Office of Religious Affairs (KUA) oroutside working hours at a rate of Rp.600,000.00 and executing it inside KUA at a rate of Rp. 0.00 orfree. The implementation of Government Regulation Number 48 of 2014 has been ineffective, due tothe lack of public interest in carrying out marriages in the KUA even though it has been free. However,the payment for the marriage registration of the KUA Kecmatan Jatiasih has been effective, this isevident when the author conducted an interview with the KUA and the community that it is true thatwhen carrying out a marriage within the KUA there is no charge and when carrying out a marriageoutside the KUA or outside working hours a rate is imposed. Rp. 600,000.00 paid at the bank.Primarydata sources were obtained from interviews and secondary data sources were obtained from books,journals and others. The type of research used in this research is the type of field research (SocioLegal Research). The research approach conducted by the author uses descriptive qualitative. Datacollection is done by the author to get and understand the picture and the existing reality, the writeruses data collection techniques by interview, observation and documents. From the data that has beencollected, then the writer analyzes using descriptive method. With the enactment of PP Number 48of 2014, it received a positive response from the upstream government because prior to the issuanceof Government Regulation Number 48 of 2014 there were many accusations of gratification thatwere shown to the head of the KUA Jatiasih District, but after the issuance of the PP there were noaccusations of gratification. However, there is still a lack of public interest in carrying out marriageswithin the KUA even though it has been made free, due to the customs of the Jatiasih Subdistrict peoplewho usually carry out marriages outside the KUA. Whether in the mosque, meeting hall or the houseof the bride and groom.